Making weight: Maintaining body mass for weight class barbell athletes - Moore, J. L.; Travis, S. K.; Lee, M. L.; Stone, M. H. (Strength and Conditioning Journal, 2019)
Weightlifting and powerlifting are strength and power sports requiring athletes to participate in precompetition weigh-ins. Many athletes attempt to gain a competitive edge over smaller competitors by reducing body mass. Although these methods may seem advantageous, there are many negative outcomes that outweigh potential positive performance effects. Manipulating body mass can be performed effectively with minimal side effects; however, weightlifters and powerlifters participating in 2-hour weigh-ins should not cut weight at the expense of optimizing strength and power adaptations.